Kajian Tahap Pengembangan Hunian Keluarga Pascagempa di Kabupaten Lombok Utara Sepanjang 2018-2022 - Andi Karina Deapati; Dahniar; Elvita Bellani (Arsir: Jurnal Arsitektur, 2025)
Five years after the 2018 Lombok earthquake, several temporary shelters and even emergency ones still exist and are being used by the community, despite the fact that the majority of them have relocated to permanent housing. In Dusun Boyotan, one extended family continues to utilize their post-earthquake dwellings, incorporating various functions related to building sustainability and cultural suitability. This research aims to present an up-to-date survey that identifies the stages of house development and explores how residents adapt to post-earthquake dwellings, as well as the reasons behind these changes. The research method employed in this study is a qualitative case study approach. Data was collected through in-depth interviews and a study of the resident's perceptions of their dwellings before and after the earthquake. The research findings indicate that the transition from emergency shelters to temporary housing involves the use of locally available materials and construction methods in the affected area. Furthermore, residents experienced an improvement in housing quality through the provision of permanent dwellings that adhere to national standards by the Indonesian government. The process of housing adaptation carried out by an extended family over four years involved behavioral adaptation and spatial adjustment in response to each housing stage and the use of new materials.